A low-cost CMOS-MEMS Piezoresistive Accelerometer With Large Proof Mass - Md Khir, Mohd Haris (MDPI, 2011)
This paper reports a low-cost, high-sensitivity CMOS-MEMS piezoresistive accelerometer with large proof mass. In the device fabricated using ON Semiconductor 0.5 μm CMOS technology, an inherent CMOS polysilicon thin film is utilized as the piezoresistive sensing material. A full Wheatstone bridge was constructed through easy wiring allowed by the three metal layers in the 0.5 μm CMOS technology. The device fabrication process consisted of a standard CMOS process for sensor configuration, and a deep reactive ion etching (DRIE) based post-CMOS microfabrication for MEMS structure release. A bulk single-crystal silicon (SCS) substrate is included in the proof mass to increase sensor sensitivity. In device design and analysis, the self heating of the polysilicon piezoresistors and its effect to the sensor performance is also discussed. With a low operating power of 1.5mW, the accelerometer demonstrates a sensitivity of 0.077 mV/g prior to any amplification. Dynamic tests have been conducted with a high-end commercial calibrating accelerometer as reference.